2021
DOI: 10.1016/j.psj.2021.101385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary direct-fed microbial and yeast cell walls on cecal digesta microbiota of layer chicks inoculated with nalidixic acid resistant Salmonella Enteritidis

Abstract: Salmonella enterica serovar Enteritidis ( SE ) has consistently been the most common serotype associated with the foodborne Salmonellosis worldwide. In this study, the effect of a dietary direct-fed microbial ( DFM ) and yeast cell walls ( YCW ) under a challenge of nalidixic acid resistant SE strain using layer chicks has been investigated. A total of 160 newly hatched Dekalb White female chicks were randomly assigned into 2 exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…In addition to the ileum and cloaca, cecal pouches are the preferred organs for SE colonization and establishment after it is ingested by chickens [35]. After an SE challenge, SE colonized the ceca of young layer pullets [21,26,29,30,36], layer pullets near sexual maturity [24,25,27,28], and adult laying hens [21][22][23]. In this study, orally infecting layer pullets with an SE dose of 6.3 × 10 7 CFU at 8 days of age resulted in colonization of the ceca, as evidenced by load and prevalence of SE in the ceca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the ileum and cloaca, cecal pouches are the preferred organs for SE colonization and establishment after it is ingested by chickens [35]. After an SE challenge, SE colonized the ceca of young layer pullets [21,26,29,30,36], layer pullets near sexual maturity [24,25,27,28], and adult laying hens [21][22][23]. In this study, orally infecting layer pullets with an SE dose of 6.3 × 10 7 CFU at 8 days of age resulted in colonization of the ceca, as evidenced by load and prevalence of SE in the ceca.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bacillus-based probiotics and yeast cell wall-based prebiotics are among the most used feed additives in poultry. Only recently, however, has there been published research, though limited, testing the effects of combinations of Bacillus and MOS on SE colonization in layer birds [23,[28][29][30]. In these publications, the synbiotics tested contained different Bacillus probiotics and yeast cell wall prebiotics and used either young pullets or adult hens of either Hy-Line or Dekalb genetics background.…”
Section: Introductionmentioning
confidence: 99%
“…Again, the authors reported no SE prevalence reduction in ceca, but in this case, reported significant mean log 10 MPN/g reductions for YCW and probiotic treatments alone, approximating adjusted means of 1.4 log 10 MPN/g, but only 0.78 log 10 MPN/g for the combined product group which was not significantly different from control [ 42 ]. The effects of a treatment containing a commercial YCW combined with a Bacillus subtilis probiotic administered to day-old layer chicks and directly challenged at 8 days with SE (2.1 × 10 9 CFU), resulted in mean cecal log 10 CFU/g reductions of 0.61, 0.49, 0.45, and 1.25 at 3, 6, 10, and 14 DPC, respectively [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…After challenged with SE, the abundance of the Firmicutes in the challenged group was higher than that of the control group, and the Bacteroidetes were significantly reduced. SE infection decreases the abundance of specific microbial genera and microbial diversity in the fecal material of laying hens and then causes dysbiosis [ 55 ]. Moreover, intestinal mucosal damage caused by SE infection leads to dysbiosis of the normal flora of the intestine, transforming intestinal flora from beneficial bacteria to pathogenic bacteria [ 56 ].…”
Section: Discussionmentioning
confidence: 99%